2004
DOI: 10.1007/s11178-005-0093-2
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic olefination. Estimation of the reactivity of polyhaloalkanes

Abstract: Global electrophilicity indices and carbon-halogen bond energies of a wide series of halogen derivatives were calculated in terms of the density functional theory (DFT). The calculated values were used to estimate the reactivity of halogen derivatives under conditions of catalytic olefination. Reactions of N-unsubstituted hydrazones with polyhaloalkanes in the presence of CuCl afforded substituted alkenes. The relation between the structure of polyhaloalkanes and their reactivity was studied using the reaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 14 publications
1
7
0
1
Order By: Relevance
“…In accordance with our model of ''catalytic olefination activity'' [21], CBr 3 CF 3 should be a very active reagent for catalytic olefination (the most reactive of all fluorinated compounds which we have used earlier) and should to provide high yields of desired products with aldehydes and ketones. The high difference in steric volumes of CF 3 group and bromine atom permit us to hope for high stereoselectivity of reaction.…”
Section: Introductionsupporting
confidence: 60%
“…In accordance with our model of ''catalytic olefination activity'' [21], CBr 3 CF 3 should be a very active reagent for catalytic olefination (the most reactive of all fluorinated compounds which we have used earlier) and should to provide high yields of desired products with aldehydes and ketones. The high difference in steric volumes of CF 3 group and bromine atom permit us to hope for high stereoselectivity of reaction.…”
Section: Introductionsupporting
confidence: 60%
“…Initial 1-aryl-2-halogeno-3,3,3-trifluoro­propenes 1a – l were obtained by reaction of aryl aldehydes with 1,1,1-trifluoro-2,2,2-trihaloethanes. To estimate the electronic properties of reaction intermediates, we performed DFT calculations (B3LYP) of cations A , B , derived from styrenes 1 (Table ). Charge distribution, contribution of atomic orbital into molecular orbital, and global electrophilicity indices ω were calculated. In “open form” cations A1 – A12 , atom C 1 bears a positive charge (0.02–0.12 e) and has a large LUMO contribution (25.9–48.1%) (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…Later, 8 it was demonstrated that bromotri chloromethane is a more reactive alkenylating reagent than tetrachloromethane, even in the presence of a cata lyst (0.5 mol. % CuCl).…”
Section: Methodsmentioning
confidence: 99%